Analysis of Income Disparities between Regions in the Western Region of Indonesia and the Eastern Region of Indonesia - Teddy Christianto Leasiwal; Rukmuin W. Payapo; Hermi Oppier; Diah Setya (GoAcademica Research & Publishing, 2022)
This study aims to analyze Income Disparities between Regions in the Western Region of Indonesia and the Eastern Region of Indonesia. The type of research used in this study is quantitative research. The variables in this study are Economic Growth. Based on the analysis, the results of this study are the provinces in the Western and Eastern regions of Indonesia are divided into four existing classifications. A total of 2 provinces, namely Jakarta and North Kalimantan Provinces, are among the fast-growing developed regions. A total of 5 provinces, namely Riau Province, Kepulauan Riau, West Papua, Banten and East Kalimantan are among the developed but depressed provinces. A total of 15 provinces namely Central Java, Southeast Sulawesi, Yogyakarta, Central Kalimantan, Jambi, North Sulawesi, Bengkulu, Central Sulawesi, South Sumatra, Maluku, West Sulawesi, North Maluku, South Sulawesi, and Gorontalo Including fast-growing provinces and as 12 provinces, namely West Sumatra, East Java, Bali, South Kalimantan, Lampung, West Kalimantan, West Java, North Sumatra, Aceh, Papua, Kepulauan Bangka Belitung and West Nusa Tenggara are among the many relatively lagging provinces.